#1**+10 **

"c" is easy.... it's = 7

The vertex is at (h, k) = (-1, 8) and the point (2. -1) is on the graph

So we have

y = a(x - h)^2 + k

-1 =a(2- (-1))^2 + 8

-1 = a(3)^2 + 8 subtract 8 from both sides

-9 = a(9) divide both sides by 9

-1 = a

And the x coordinate of the vertex is given by -b/2a

So we have

-1 = -b/2(-1) → -1 = -b/-2 → b = - 2

So.....our function is

y = -1x^2 - 2x + 7

So

a + b + 2c =

-1 + (-2) + 2(7) =

11

CPhill
Nov 25, 2014

#1**+10 **

Best Answer

"c" is easy.... it's = 7

The vertex is at (h, k) = (-1, 8) and the point (2. -1) is on the graph

So we have

y = a(x - h)^2 + k

-1 =a(2- (-1))^2 + 8

-1 = a(3)^2 + 8 subtract 8 from both sides

-9 = a(9) divide both sides by 9

-1 = a

And the x coordinate of the vertex is given by -b/2a

So we have

-1 = -b/2(-1) → -1 = -b/-2 → b = - 2

So.....our function is

y = -1x^2 - 2x + 7

So

a + b + 2c =

-1 + (-2) + 2(7) =

11

CPhill
Nov 25, 2014